Treatment and outcomes of hepatocellular carcinoma in patients with Sickle cell disease: a population-based study in the U.S. Issue 2 (February 2022) - Barbetta, Arianna; Goldbeck, Cameron; Lim, Angelina; Martin, Sean P.; Kahn, Jeffrey A.; Sheikh, M. Raashid; Emamaullee, Juliet
Abstract: Background: Sickle cell disease (SCD) is a rare hemoglobinopathy which can result in chronic liver disease and cirrhosis. Patients with SCD have an increased risk of hematologic malignancy, but the prevalence of hepatocellular carcinoma (HCC) in this population is unknown. Herein, the association of SCD with HCC was examined using registry data. Methods: The SEER-Medicare database was queried to identify patients diagnosed with HCC between 2000 and 2015, and further stratified by SCD status. Propensity matching was performed to examine cancer-related survival and treatment outcomes. Results: Overall 56, 934 patients with HCC were identified, including 81 patients with SCD. Patients with SCD more frequently had cirrhosis [48.1% (39/81) vs 23.5% (13, 377/56, 853), p < 0.01] yet presented with smaller tumors [<5 cm: 51.9% (42/81) vs 38.5% (21, 898/56, 853), p = 0.01]. After propensity matching, SCD was not associated with attenuated survival (aHR 0.73 95%CI 0.52–1.01). When stratified by treatment, patients with SCD had equivalent outcomes to chemotherapy (p = 0.65), TACE/TARE (p = 0.35), resection (p = 0.15) and transplantation (p = 0.67) when compared to non-SCD patients. Conclusion: This study confirms that a subset of patients with SCD will develop HCC. Importantly, therapeutic options for HCC should not be limited by pre-existing SCD, and similar survival should be expected when compared to non-SCD patients. Graphical abstract: Image 1